PEMBERDAYAAN MASYARAKAT MANTAN BURUH MIGRAN KORBAN TRAFFICKING DI KABUPATEN WONOSOBO - Tissa Silvia; Sugi Rahayu (Yogyakarta State University, 2017)
This research This research aimed to analyze the community empowerment of ex-migrant labors in Kampung Buruh Migran (KBM) of Tracap Village, Kaliworo sub-district, Wonosobo regency. This research result in the implementation of ex migrant empowerment was implemented by strengthening the economic capacity and human capacity. In the implementation of ex migrant empowerment there was decreased of level participation from ex migrant labors, from 297 members: recorded 72 members following empowerment in 2012 and now it was decreasing to 29 active mambers. Succesfull empowerment activity in strengthening economic capacity were koperasi and saving and loan. Meanwhile unseccesfull empowerment activities were farming and agriculture activities. The strengthening capacity and socialization were not yet effective. The empowerment were conducted in seven steps of empowering. The resistans factors were low quality of human resources, lack of coordination with government, the support expectation of targeted community to obtain goods and money, and lack of governments interventation toward the sustainability of the program.Keyword: Empowerment, Ex Migrant Labor, and Kampung Buruh Migran